A SEMANTIC ANALYSIS ON SPOTIFY TOP SONGS FOR TEENS - Siwi Isnuhoni; Chandraswari Swastya Respati (Journal of Research on Applied Linguistics, Language, and Language Teaching, 2019)
Songs was stated as a learning material in Curriculum 2013. Teachers are expected to teach the students on the social function and linguistic elements embodied in song lyrics. Moreover, the teachers could use Spotify as a media to provide songs for learning materials because Spotify was one of the well-known music platform. However, not all songs in Spotify were suitable enough for learning material. Therefore, this research was aimed to examine content words found on the top five songs lyric on Spotify. The analysis used Semantic Analysis which is a method to classify words according to their meanings. The analysis showed all of the lyrics frequently used Human noun, action verb, mental verb, stative and personal opinion adjective.